Guide to the Bible - Smith, Carol (Urichsville, Ohio : Humble Creek, 2002)
A simple introductory guide to the Bible with time lines, definitions, and book-by-book synopses.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Introductions; Bible -- History of Biblical events